1989
DOI: 10.1161/01.str.20.7.904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mild hypothermia on ischemia-induced release of neurotransmitters and free fatty acids in rat brain.

Abstract: We have demonstrated previously that mild intraischemic hypothermia confers a marked protective effect on the final histopathological outcome. The present study was carried out to evaluate whether this protective effect involves changes in the degree of local cerebral blood flow reductions, tissue accumulation of free fatty acids, or alterations in the extracellular release of glutamate and dopamine. Rats whose intraischemic brain temperature was maintained at 36° C, 33° C, or 30° C were subjected to 20 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
348
0
5

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,044 publications
(362 citation statements)
references
References 39 publications
9
348
0
5
Order By: Relevance
“…Hypothermia has been shown to decrease intracellular acidosis caused by ischemia (Norwood and Norwood, 1982), reduce the metabolic require ments of the brain (Siesjo, 1978), and significantly ameliorate trauma-induced edema (Clasen et aI., 1968). Of particular relevance to fluid percussion injury, however, Busto et al (1989) have demon strated that moderate cerebral hypothermia (30°C) dramatically attenuates the levels of excitotoxins (glutamate and aspartate) accumulating after isch emic injury. Fluid percussion injury in rats, of the type reported here, produces a significant increase in excitatory glutamate (Faden et al, 1989;Katayama et aI., 1990) and acetylcholine (Gorman et aI., 1989) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia has been shown to decrease intracellular acidosis caused by ischemia (Norwood and Norwood, 1982), reduce the metabolic require ments of the brain (Siesjo, 1978), and significantly ameliorate trauma-induced edema (Clasen et aI., 1968). Of particular relevance to fluid percussion injury, however, Busto et al (1989) have demon strated that moderate cerebral hypothermia (30°C) dramatically attenuates the levels of excitotoxins (glutamate and aspartate) accumulating after isch emic injury. Fluid percussion injury in rats, of the type reported here, produces a significant increase in excitatory glutamate (Faden et al, 1989;Katayama et aI., 1990) and acetylcholine (Gorman et aI., 1989) levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mild hypothermia completely blocks (Busto et al, 1989b;Li et al, 1999;MartinezTica and Zornow, 2000;Patel et al, 1994), partially blocks Winfree et al, 1996;Yamamoto et al, 1999), merely delays (Asai et al, 2000(Asai et al, , 1998, or does not inhibit an increase in [Glu] e after cerebral ischemia (Berger et al, 1998;Zhao et al, 1997). Furthermore, the effect of hypothermia on [Glu] e depends on the brain area, ischemic severity, and animal age (Berger et al, 2002;Lo et al, 1993;Van Hemelrijck et al, 2003).…”
Section: Glutamate Releasementioning
confidence: 99%
“…Intraischemic hypothermia delays or attenuates both ATP depletion (Ibayashi et al, 2000;Sutton et al, 1991;Welsh et al, 1990) and anoxic depolarization (Bart et al, 1998;Nakashima and Todd, 1996;Takeda et al, 2003), it also blocks glutamate release (Busto et al, 1989b;Patel et al, 1994;Winfree et al, 1996), suppresses inflammation (Kawai et al, 2000;Wang et al, 2002), maintains the integrity of the BBB (Dietrich et al, 1990;Huang et al, 1999;Kawanishi, 2003), reduces free radical production , inhibits protein kinase C translocation (Cardell et al, 1991;Shimohata et al, 2007a, b;Tohyama et al, 1998), inhibits matrix metalloproteinase expression (Hamann et al, 2004), and blocks both necrosis and apoptosis. Intraischemic hypothermia also preserves the base-excision repair pathway, which repairs oxidative damage (Luo et al, 2007).…”
Section: The Ostensible Pan-inhibitive Effects Of Hypothermiamentioning
confidence: 99%
“…Excess glutamate triggers the excitotoxic cascade that can ultimately result in cell injury and death [39]. Even mild decreases in temperature have been shown to ameliorate these detrimental effects [40][41][42]. Brain injury activates the inflammatory/ immune response [43,44].…”
Section: Detrimental Effects Of Fevermentioning
confidence: 99%